2022
DOI: 10.3390/en16010186
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Scheduling of Battery-Swapping Station Loads for Capacity Enhancement of a Distribution System

Abstract: A battery-swapping station (BSS) can serve as a flexible source in distribution systems, since electric vehicle (EV) batteries can be charged at different time periods prior to their swapping at a BSS. This paper presents an EV battery service transformation from charging to swapping batteries for EVs for the capacity enhancement of a distribution system. A novel mathematical model is proposed to optimally quantify and maximize the flexibility of BSS loads in providing demand response for the utility operator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition, [18] aims to minimize the total single-day cost of a battery swapping station serving EBs by considering the demand response. In another study [19], the effect of replacing charging stations with BSS on the power system is examined in a 32-bus system.…”
Section: A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, [18] aims to minimize the total single-day cost of a battery swapping station serving EBs by considering the demand response. In another study [19], the effect of replacing charging stations with BSS on the power system is examined in a 32-bus system.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Research Gap Research Topic Methodology [6], [14]- [19] The placement problem has not been studied. Optimization of BSS operation Novel optimization/strategy models for BSS operation.…”
Section: Studymentioning
confidence: 99%
“…The optimal charging schedule of BSSs catering to electric buses (EBs) was investigated in [7,8]. Furthermore, the objective of [9,10] is to reduce the overall cost of a BSSs facility that caters to EVs within a single day. Demand response is a factor in achieving this.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a great need for renewable hydrocarbon fuels on a global scale, and rules to lessen the negative effects of industry on the environment are also being implemented. [6][7][8] Both the industrial need for an alternative fuel that is free of pollutants and the need for HDO will be satised by the HDO reaction. 9,10 Previous studies have shown the transformation of non-food oils such as long chain fatty acids, palm oil, jatropha oil, and microalgae oil into hydrocarbons using a variety of catalysts.…”
Section: Introductionmentioning
confidence: 99%